Service Continuity Management in Health Emergenciesand Disasters: Approach for Productive Reactivation - Artavia Pereira, Catalina (2021)
This article describes the elaboration and content process of the normative document of sectorial protocols for productive sector reactivation in the case of Costa Rica. Its main objective is to present how the government measures evolve to respond to health emergencies through sectorial protocols for service continuity and productive sectors. It is argued that the continuity of operations in public and private organizations is even more relevant and a priority in the event of multiple threats influencing the stability of the economic, social and political system. The methodology used for the sectorial protocol development was based on the bibliographic review and other countries experiences in the protocol elaboration, and the recommendations through the health guidelines for COVID-19. In conclusion, the importance of public policy instruments issued in the face of emergencies and health disasters. JEL: I1 Analysis of health care markets.